Budowanie więzi w rodzinnych formach opieki = Building ties of family forms of care - Prokosz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The bonds between members of a traditional family are shaped naturally. In case of other forms of care-giving (adoptive, foster family or children?s home) such bond can only be established from the moment of setting up a new family. This article tackles the issue of the essential information on family bonds and ways of its establishing and strengthening, feasible to be applied in the family forms of the care-giving.
Keywords: więzi rodzinne; budowanie więxi; umacnianie więzi; rodzinne formy opieki; family bonds; establishing bonds; strengthening bonds; foster family care